Integrative analyses of leprosy susceptibility genes indicate a common autoimmune profile. Issue 1 (April 2016) - Zhang, Deng-Feng; Wang, Dong; Li, Yu-Ye; Yao, Yong-Gang
Highlights: We highlighted a list of hub leprosy risk genes. Leprosy risk genes were enriched in activation and regulation of immune response. Hub leprosy susceptibility genes compose co-evolution networks. Lepromatous and tuberculoid leprosy have similar risk gene expression pattern. Leprosy susceptibility genes were largely shared by autoimmune diseases. Abstract: Background: Leprosy is an ancient chronic infection in the skin and peripheral nerves caused by Mycobacterium leprae . The development of leprosy depends on genetic background and the immune status of the host. However, there is no systematic view focusing on the biological pathways, interaction networks and overall expression pattern of leprosy-related immune and genetic factors. Objectives: To identify the hub genes in the center of leprosy genetic network and to provide an insight into immune and genetic factors contributing to leprosy. Methods: We retrieved all reported leprosy-related genes and performed integrative analyses covering gene expression profiling, pathway analysis, protein–protein interaction network, and evolutionary analyses. Results: A list of 123 differentially expressed leprosy related genes, which were enriched in activation and regulation of immune response, was obtained in our analyses. Cross-disorder analysis showed that the list of leprosy susceptibility genes was largely shared by typical autoimmune diseases such as lupus erythematosus and arthritis, suggesting that similar pathways might be affected in leprosy and autoimmune diseases. Protein–protein interaction (PPI) and positive selection analyses revealed a co-evolution network of leprosy risk genes. Conclusions: Our analyses showed that leprosy associated genes constituted a co-evolution network and might undergo positive selection driven by M. leprae . We suggested that leprosy may be a kind of autoimmune disease and the development of leprosy is a matter of defect or over-activation of body immunity.